The Effect of Visual Auditory, Kinesthetic Learning Styles on Students' Learning Interest at Christian Junior High School - Nani Setiawati; Susmita Irene; Orbit Thomas; Rinto Alexandro; Kharisma Nugraha Putra (Indonesian Journal Of Educational Research and Review, 2023)
The problem that is often found in students is the difficulty of students in accepting subject matter which is effected by the learning style that students have. Student learning styles encourage students to gain interest and better learning outcomes. This study aimed to analyze the effect of visual, auditory, and kinesthetic learning styles on the learning interest of Christian Junior School students. This type of research was quantitative research. The sample in this study comprised all students of Christian Junior High School from grades VII and VIII, totaling 61 students. The data collection method was a survey using a questionnaire. Data were analyzed using multiple linear regression analysis using SPSS 20 software. The results showed that the visual, auditory, and kinesthetic learning styles had an effect on students' interest in learning at Christian Junior High School. In addition, the results of the study also found that kinesthetic learning style was a student learning style that had the most significant effect on student learning interest at 84,3%. In conclusion, the research findings indicate that students' learning interest is significantly affected by their learning styles. Individuals who are familiar with their learning styles can take essential steps to learn faster and more easily, resulting in desired learning outcomes.